2014
DOI: 10.1101/sqb.2014.79.024778
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Hows and Whys of Decision-Making: From Expected Utility to Divisive Normalization

Abstract: Over the course of the last century, economists and ethologists have built detailed models from first principles of how humans and animals should make decisions. Over the course of the last few decades, psychologists and behavioral economists have gathered a wealth of data at variance with the predictions of these economic models. This has led to the development of highly descriptive models that can often predict what choices people or animals will make but without offering any insight into why people make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Consistently with these findings, functional imaging studies of decision making in man have retrieved sparse cortical signals from the regression of the signal on the difference between the decision values of the chosen and non-chosen options (Heekeren et al 2008). It has also been argued that this mechanism may also apply to preference-based choice (Krajbich and Rangel 2011;Cisek 2012;Glimcher 2015), and to choices in social cognition (Shadlen and Kiani 2013), where evidence in this respect remains scant (Ruff and Fehr 2014).…”
Section: Segregation Connectivity and Gradients Of Deactivation In mentioning
confidence: 88%
“…Consistently with these findings, functional imaging studies of decision making in man have retrieved sparse cortical signals from the regression of the signal on the difference between the decision values of the chosen and non-chosen options (Heekeren et al 2008). It has also been argued that this mechanism may also apply to preference-based choice (Krajbich and Rangel 2011;Cisek 2012;Glimcher 2015), and to choices in social cognition (Shadlen and Kiani 2013), where evidence in this respect remains scant (Ruff and Fehr 2014).…”
Section: Segregation Connectivity and Gradients Of Deactivation In mentioning
confidence: 88%
“…Thus, when a behavior delivers a result better than predicted, certain neurons reward the 'choosing circuits' by secreting a pulse of dopamine. This encourages the brain to store the memory and repeat the behavior ( Glimcher, 2014 ; Schultz, 2015 ). This type of reward learning is mathematically optimal, and since it is present in the fruit fly, it was probably already present in the brain of our last common ancestor the urbilaterian worm.…”
Section: Multi-cellularity Expanded Resources and Computational Capacmentioning
confidence: 99%
“…This appendix is intended to supply the interested reader with a brief overview of the origins and ubiquity of the normalization forms in the neuroscientific literature. A more detailed review can be found in Glimcher (2014).…”
Section: Appendix a Background On The Normalization Computationmentioning
confidence: 99%